Russian Language Development of Communicative Competencies of Students in Classes (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article covers the goals and objectives of the lessons of the Russian language, the development of communicative competencies of students. The opinions of pedagogical scientists on communicative competence are also described.